2011
DOI: 10.2298/sarh1106333i
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative air testing of colorectal anastomoses

Abstract: In our opinion, intraoperative air testing of colorectal anastomosis is a good method for prevention of anastomotic dehiscence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 5 publications
1
38
0
2
Order By: Relevance
“…Of note, the highest clinical leak rates occurred in patients with a positive air‐leak test who had suture repair alone (12·2 per cent); rates were zero among patients who had faecal diversion or reanastomosis. Furthermore, a study in 2011 demonstrated a trend towards lower leak rates with air‐leak testing; however, the study was underpowered.…”
Section: Intraoperative Risk Factorsmentioning
confidence: 99%
“…Of note, the highest clinical leak rates occurred in patients with a positive air‐leak test who had suture repair alone (12·2 per cent); rates were zero among patients who had faecal diversion or reanastomosis. Furthermore, a study in 2011 demonstrated a trend towards lower leak rates with air‐leak testing; however, the study was underpowered.…”
Section: Intraoperative Risk Factorsmentioning
confidence: 99%
“…The thirteen reviewed studies included a total of N=3,023 patients (Table 3), [16,17,[19][20][21][22][23][24][25][26][27][28][29]. Study sample size and design was variable.…”
Section: Resultsmentioning
confidence: 99%
“…Suture repair (74.7%) was the most common method of anastomosis correction used followed by takedown and re-anastomosis (17.3%) and diversion (8.0%). No significant differences in intraoperative leak rates were found were found across anastomosis types (staple: 4.9%, suture: 2.3%, and compression: 0.0%, p=0.066) in the 10 studies that reported leak based on type of anastomosis employed [16,[19][20][21][22][24][25][26][27][28]. Six articles reported on the rate of intraoperative leaks by surgical technique used (laparoscopic v. open) [22,[25][26][27][28][29].…”
Section: Search Term Description Definitionmentioning
confidence: 94%
See 1 more Smart Citation
“…Another study found that intrarectal pressure could not be raised above 35 mm Hg because of venting of air [27]. Insufflation is typically performed until the rectum is 'optimally' distended, which may be limited by air leak along the sigmoidoscope [28]. Based on these observations we have chosen 30 mmHg as a reasonable leak pressure criteria to assess the quality of a circular stapler in creating a secure anastomosis.…”
Section: Discussionmentioning
confidence: 99%